The Effect Of Wordwall-Assisted Teams Games Tournament Learning Model On Students' Critical Thinking Abilities In Biology Subjects - Handoko, Akbar; Oktafiani, Raicha; Dianisari, Ike; Ferry, Dharma; Mazalena, Mazalena (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2025)
This research aims to determine the effect of the teams games tournament learning model assisted by wordwall on students' critical thinking abilities in biology subjects. This research is quantitative research with a quasi experimental design method. The design used is a pretest posttest control group design. The sampling technique in this research used a cluster random sampling technique for class XII IPA 2 (experimental class) and XII IPA 3 (control class). Data collection techniques in this research consisted of tests, field notes, and documentation. The analysis test used is the independent t-test for critical thinking abilities, showing that Sig. (2-tailed) is 0.000 <α (0.05), then H0 is rejected and H1 is accepted. So the results of this research can be concluded that there is an influence of using the teams games tournament learning model with the help of wordwall on students' critical thinking abilities in biology subjects. Pengaruh Model Pembelajaran Turnamen Game Tim Berbantuan Wordwall Terhadap Kemampuan Berpikir Kritis Siswa Dalam Mata Pelajaran Biologi ABSTRAK: Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran teams games tournament berbantu wordwall terhadap kemampuan berpikir kritis peserta didik pada mata pelajaran biologi. Penelitian ini adalah penelitian kuantitatif dengan jenis metode quasy experimental design. Desain yang digunakan yaitu pretest posttest kontrol group design. Teknik sampling dalam penelitian ini menggunakan teknik cluster random sampling diperoleh kelas XII IPA 2 (kelas eksperimen) dan XII IPA 3 (kelas kontrol). Teknik pengumpulan data dalam penelitian ini terdiri dari tes, catatan lapangan, dan dokumentasi. Uji analisis yang digunakan adalah uji-t independent kemampuan berpikir kritis menunjukan bahwa Sig. (2-tailed) sebesar 0,000 (0,05), maka H0 ditolak dan H1 diterima. Sehingga hasil penelitian ini dapat disimpulkan bahwa terdapat pengaruh penggunaan model pembelajaran teams games tournament berbantu wordwall terhadap kemampuan berpikir kritis peserta didik pada mata pelajaran biologi.